Endodontic management of three-rooted maxillary second premolar in a patient with bilateral occurrence of three roots in maxillary second premolars - Chauhan, Raju (Medicina Oral S.L., 2012)
The possibility of bilateral maxillary second premolars having three separate roots is quite low; however, it must be taken into account in clinical and radiographic evaluations during endodontic treatment. A correct clinical and radiographic diagnosis based on knowledge of root canal anatomy and critical interpretation of radiographs is necessary for a safer and successful endodontic treatment of these teeth. Failure of root canal treatment can occur due to missed roots/canals and often diagnosed when patient experiences continuous post-operative pain and discomfort. This case report describes the root canal treatment of a three-rooted maxillary second premolar in a patient with bilateral occurrence of three roots in maxillary second premolars. Key words:Anatomic variations, maxillary second premolar, radiculous.